Kewenangan Badan Pengawas Pemilu (Bawaslu) Dalam Menyelesaikan Pelanggaran Administrasi Pada Pemilihan Kepala Daerah Ditinjau Dari Putusan Mahkamah Konstitusi Nomor 104/Puu-Xxiii/2025 Perspektif Siyasah Dusturiyah - Adlin, Muhammad Nur; Batubara, Putri Eka Ramadhani (Lex Stricta : Jurnal Ilmu Hukum, 2025)
This study analyses changes in the authority of the Election Supervisory Agency (Bawaslu) in resolving administrative violations in regional head elections following Constitutional Court Decision No. 104/PUU-XXIII/2025 from the perspective of Siyasah Dusturiyah. Using a legal-normative approach and conceptual analysis, this study examines the shift in Bawaslu's position from a recommendatory supervisory body to a quasi-judicial body with the authority to issue final and binding administrative decisions. The results of the study show that strengthening Bawaslu's authority reinforces legal certainty, increases the effectiveness of supervision, and creates balance between election organisers. From a Siyasah Dusturiyah perspective, this policy reflects the implementation of the values of hisbah, ʿadl, and amanah in modern political governance. Normatively and empirically, the synergy between constitutional law and Islamic sharia values strengthens the moral and legal legitimacy of fair and integrity-based election supervision.